Proceedings of the 1999 Congress on Evolutionary Computation-Cec99 (Cat. No. 99TH8406)
DOI: 10.1109/cec.1999.782662
|View full text |Cite
|
Sign up to set email alerts
|

Local search operators in fast evolutionary programming

Abstract: Previous studies have shown that embedding local search in classical evolutionary programming (EP) could lead to improved performance on function optimization problems. In this paper, the utility of local search is investigated with fast evolutionary programming (FEP) and comparisons are offered between performance improvements obtained when using local search with Gaussian and Cauchy mutations. Experiments were conducted on a suite of four well known function optimization problems using two local search metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 11 publications
0
6
0
1
Order By: Relevance
“…Cauchy distribution, on the other hand, is a more slowly decaying distribution in comparison with Gaussian and allows even the large mutation step sizes. Cauchy distribution has reportedly outperformed Gaussian distribution in several instances available in literature (Lan and Lan 2008;Rudolph 1997;Yao et al 1999;Birru et al 1999;Wang et al 2006;Coelho and Krohling 2003).…”
Section: Application Of Cauchy Mutationmentioning
confidence: 97%
“…Cauchy distribution, on the other hand, is a more slowly decaying distribution in comparison with Gaussian and allows even the large mutation step sizes. Cauchy distribution has reportedly outperformed Gaussian distribution in several instances available in literature (Lan and Lan 2008;Rudolph 1997;Yao et al 1999;Birru et al 1999;Wang et al 2006;Coelho and Krohling 2003).…”
Section: Application Of Cauchy Mutationmentioning
confidence: 97%
“…In the standard DE new individuals are generated with the information of different individuals which may leads to good explorative global searching power, but the local searching power near each individual especially the best ones is relatively poor. An early published paper about evolutionary programming (Birru et al 1999) also indicated that local searching helps to generate global optimum if the corresponding algorithm could find the basin of attraction for global optimum and thus reduce the time for the algorithm to converge. Thus the explorative power and exploitive power should be balanced to reach better performance.…”
Section: Introductionmentioning
confidence: 99%
“…A successful MA is an algorithm composed of several well-coordinated components with a proper balance between the global and the local search, which improves the efficiency of searches [2]. Many MAs have been applied to numerical optimization problems, such as a hybrid genetic algorithm with local search (GA-LS) [3], [4], [5], differential evolution with local search (DE-LS) [2], [6], [7], particle swarm optimization with local search (PSO-LS) [8], [9], [10], and evolutionary programming with local search (EP-LS) [11]. Genetic algorithms (GAs) [12] are a very popular class of EAs, they are the most studied population based algorithms.…”
Section: Introductionmentioning
confidence: 99%